Evaluation of Bile salt hydrolase activity and cholesterol-binding ability of lactic acid bacteria isolated from milk and meconium - Dung Nguyen Thi*, Trang Nguyen Thi Thuy, Toan Nguyen Van, Tu Bui Le Kha, Hong Dao Nu Dieu, Lieu Nguyen Thi (Vietnam Journal of Science, Technology and Engineering, 2026)
Lactic acid bacteria (LAB) have long been recognised as probiotics that support the digestive system and help maintain host health. Beyond their typical features, such as tolerance to low pH, high salt concentrations, adherence to host tissues, and diverse metabolic capabilities that produce a range of beneficial compounds, LAB strains with Bile salt hydrolase (BSH) activity have been implicated in cholesterol reduction. This study isolated eight strains of LAB from human milk, cow’s milk, and meconium. The eight LAB strains were then investigated for BSH production, BSH activity, and cholesterol-binding properties. Notably, all eight strains demonstrated robust bile salt tolerance to ox gall and bile salts (including cholic acid and taurocholic acid) after 20 hours of cultivation. BSH enzyme activity varied, ranging from 0.28 to 18.04 U/ml, while cholesterol binding ranged from 34.38 to 104.02 µg/ml. Among the strains evaluated, SMB68, SMB33, and LS13 stood out as superior candidates; these strains were identified as Ligilactobacillus salivarius (L. salivarius), Enterococcus faecalis (E. faecalis), and Lactiplantibacillus plantarum (L. plantarum), respectively. Cholesterol-binding values reached 108.02, 107.33, and 81.94 µg/ml, respectively. These strains hold potential for application in products aimed at preventing lipid-related diseases